The winding road to the construction of Un Cuarto Propio. Testimonial account (Altre Modernità, 2023)
The winding road to the construction of Un Cuarto Propio. Testimonial account
Keywords: Chilean publishing houses; Un Cuarto Propio publishing house; testimony; feminist writing; dictatorship and culture